nanoparticle on PBM PENGARUH KECEPATAN PUTAR MOTOR PENGGERAK PLANETARY BALL MILL PADA PENGGILINGAN SERBUK MIKRO SiC TERHADAP KARAKTERISTIK SERBUK SiC - yousak indro nyuswantoro (Jurusan Teknik Mesin, 2022)
Nanotechnology is a technology that operates at the announced nanoscale 1-100 nm. Planetary ball mill is one of the tools used to make materials displayed on nano. In this study, SiC powder is used which is a carbide compound and is a non-oxide ceramic material. The parameters used are the variable speed of the driving motor (150 and 200) Rpm with the time during grinding for 2 hours, with the constant variable BPR 20:1 with the diameter of the grinding ball used 5 mm and 10 mm and the volume of the bowl used 250 ml made of of alumina ceramics. SiC powder will be tested using a light microscope with a magnification of 100 times to determine the size and shape of the particles. The shape of SiC particles that appear to be in the form of irregular variations (150 Rpm & 2 hours) with an average size of 49.35μ (200 Rpm & 2 hours) has an uneven particle shape with an average size of 23.78μ